Literary Translation in Periodicals : Methodological Challenges for a Transnational Approach. - Fólica, Laura. (Benjamins Translation Library, 2020)
Literary Translation in Periodicals argues that there is a pressing need for an analytical focus on translation in periodicals, a collaborative network of researchers, and a transnational and interdisciplinary approach.